2021
DOI: 10.1523/eneuro.0208-21.2021
|View full text |Cite|
|
Sign up to set email alerts
|

3D-Printed Pacifier-Shaped Mouthpiece for fMRI-Compatible Gustometers

Abstract: The authors would like to thank Alain Hugon for his major contribution in the early stages of the design of the pacifier-shaped mouthpiece, Dr. Vanessa Sennwald for her insightful comments on the manuscript, Asli Erdemli for her useful comments on the data acquisition, and Lavinia Wuensch for her work on the data preprocessing. We also thank all the people from the Brain and Behavior Lab as well as from the Perception and Bioresponses Department of the Research and Development Division of Firmenich, SA for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In a nutshell, a 3D-printed paci er-shape fMRI mouthpiece paired with a gustometer was used to deliver liquids while participants were lying down. As demonstrated in Muñoz-Tord et al [10], this allows a precise, reliable and comfortable liquid delivery. The collection of the responses was controlled by a computer running MATLAB (version R2015a; MathWorks, Natick, USA).…”
Section: Taste Stimuli and Presentationmentioning
confidence: 85%
See 4 more Smart Citations
“…In a nutshell, a 3D-printed paci er-shape fMRI mouthpiece paired with a gustometer was used to deliver liquids while participants were lying down. As demonstrated in Muñoz-Tord et al [10], this allows a precise, reliable and comfortable liquid delivery. The collection of the responses was controlled by a computer running MATLAB (version R2015a; MathWorks, Natick, USA).…”
Section: Taste Stimuli and Presentationmentioning
confidence: 85%
“…The data reported here were acquired in the context of a larger study, components of which have been [10] and will be reported separately. More precisely, we conducted this randomized, single-centre, double-blind, placebo-controlled, parallel group, prospective clinical trial from March 7, 2018, through March 18, 2020, in the Geneva University Hospitals (Switzerland), i.e.…”
Section: Trial Overviewmentioning
confidence: 99%
See 3 more Smart Citations